GLOBALIZATION PROCESS AND THE ROLE OF HUMANITIES IN THE DEVELOPMENT OF EDUCATION (International journal of artificial intelligence, 2024)
This article analyzes the impact of globalization on the education system and the development of the humanities. The digitization of education, its integration with information technologies, and the role of the humanities in the formation of universal human values, the preservation of national cultural heritage, and the development of social responsibility are discussed.